Assessment of Practices and Gaps in the Diagnosis, Management, and Follow-up of Newborns with Hypoxic-Ischemic Encephalopathy in Jordan: A Survey of Practicing Neonatologists and Pediatricians - Badran , Eman; Rawajbeh, Ahmad; Alhaj , Waseem; Elqunj, Abdallah; AL-Qhaiwi, Ala’a; Qawasmeh, Rafeef; Alhalaki, Majd; Askar, Mohammad; Al Jammal, Maryam (Jordan Medical Journal, 2025)
Background and Aims: To identify care gaps in newborns with HIE, and evaluate the practices of neonatologists and pediatricians in Jordan. The impact of HIE as Jordan's fourth top cause of infant mortality is highlighted. Methods: A cross-sectional survey of 15 neonatologists and 42 pediatricians in Jordan was conducted. A 35-item questionnaire was used to collect data on demographics, diagnosis criteria, management approach, and follow-up services. Results: The participants reported that 70% used Apgar for neonatal assessment and SARNAT staging for HIE severity. 30% of neonates were transferred to intensive care, 70% began therapeutic hypothermia within 6 hours, and 63.2% continued for 72 hours. There was a limited access to brain imaging. Conclusion: To improve neonatal care in Jordan, an organized HIE practice bundle is recommended.